Penerapan Kontrak Pelayanan (Citizen Charter) pada Rumah Sakit Umum Daerah Kabupaten Sinjai - Riskasari Riskasari; Hamrun Hamrun (Jurnal Ilmiah Ilmu Administrasi Publik, 2017)
This study aims to determine the extent to which the Service Contract (Citizen Charter) is applied to RSUD Kabupaten Sinjai. Implementation of Service Contracts is inseparable from the willingness, awareness and also cooperation between stakeholders, especially the RSUD with the community served. . This research uses qualitative approach, with case study method. For the purposes of data collection, the researchers conducted observations and in-depth interviews. The results of this study indicate that in order to improve the quality of health services that are responsive, transparent and accountable requires the application of indicators of Service Contract (Citizen Charter) optimally; provide service certainty covering time, cost, procedure and mode of service, provide information on the rights and obligations of service users, service providers, and other stakeholders in the overall process of service delivery, facilitate service users, citizens, and other stakeholders to control the practice of service delivery, service management improves service delivery performance, helps service management identify needs, expectations, and aspirations of other stakeholder service users.